Muscle Damage Indicated by Maximal Voluntary Contraction Strength Changes From Immediately to 1 Day After Eccentric Exercise of the Knee Extensors - Shoji, Mikio; Ema, Ryoichi; Nosaka, Kazunori; Kanda, Akihiro; Hirata, Kosuke; Akagi, Ryota (Frontiers in Physiology, 2021)
The present study examined if the magnitude of changes in indirect muscle damage markers could be predicted by maximal voluntary isometric contraction (MVIC) torque changes from immediately to 1 day after eccentric exercise. Twenty-eight young men performed 100 maximal isokinetic (60°/s) eccentric contractions of the knee extensors. MVIC torque, potentiated doublet torque, voluntary activation (VA) during MVIC, shear modulus of rectus femoris (RF), vastus medialis and lateralis, and muscle soreness of these muscles were measured before, immediately after and 1–3 days post-exercise. Based on the recovery rate of the MVIC torque from immediately to 1 day post-exercise, the participants were placed to a recovery group that showed an increase in the MVIC torque (11.3 to 79.9%, n=15) or a no-recovery group that showed no recovery (−71.9 to 0%, n=13). No significant difference in MVIC torque decrease immediately post-exercise was found between the recovery (−33±12%) and no-recovery (−32±9%) groups. At 1–3 days, changes in MVIC torque (−40 to −26% vs −22 to −12%), potentiated doublet torque (−37 to −22% vs −20 to −9%), and proximal RF shear modulus (29 to 34% vs 8 to 15%) were greater (p<0.05) for the no-recovery than recovery group. No significant group differences were found for muscle soreness. The recovery rate of MVIC torque was correlated (p<0.05) with the change in MVIC torque from baseline to 2 (r=0.624) or 3 days post-exercise (r=0.526), or peak change in potentiated doublet torque at 1–3 days post-exercise from baseline (r=0.691), but not correlated with the changes in other dependent variables. These results suggest that the recovery rate of MVIC torque predict changes in neuromuscular function but not muscle soreness and stiffness following eccentric exercise of the knee extensors.